Gambaran Pengelolaan Obat Di Instalasi Farmasi Rsud Provinsi Sulawesi Barat - riady, ninda thiara; Nurlina, Nurlina; Purnamasari, Vina (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Hospital Pharmacy Installation (IFRS) is a functional implementing unit organizes all pharmaceutical service activities in hospitals, which functions to carry out the management of pharmaceutical supplies with the stages of selecting, planning, procuring, storing, distributing, controlling, deleting, recording and reporting. This study aims to determine the stages of management of pharmaceutical supplies in West Sulawesi Provincial Hospital using descriptive qualitative research through interviews and observation (observation). In this study guided interviews that have been arranged systematically using a check list. The results of this study reveal that the management of pharmaceutical preparations in the Pharmacy Installation of the West Sulawesi Provincial Hospital has been effective and efficient from several aspects of management which shows a percentage of 80-100%. However, the procurement and storage aspect are still inefficient because the expenditure has not gone through the e-catalog and there is no fire extinguisher. The drug management system at the Pharmacy Installation of the West Sulawesi Provincial Hospital is in accordance with the Regulation of the Minister of Health of the Republic of Indonesia No. 72 of 2016 and Technical Guidelines for Pharmaceutical Standards in Hospitals in 2019.